Using Ecological Concepts In Interdisciplinary Physics Education (Journal of Pedagogical Inventions and Practices, 2025)
This article highlights the pressing need to fundamentally change our perspectives on the environment, to find solutions to ecological problems, to anticipate potential consequences, and to maintain stability while ensuring the harmony of nature and humanity. In order to gain a comprehensive understanding of nature and its laws, it is essential to foster students’ ecological thinking, worldview, and culture. By integrating ecological concepts into physics curricula through interdisciplinary connections, students can see how physics topics intersect with environmental knowledge. Moreover, the 6th-grade “Natural Sciences” curriculum in secondary schools—particularly its sections on “Structure of Matter” and “Ecology and Sustainable Development”—can help lay the groundwork for deepening students’ understanding of biology, geography, physics, chemistry, and astronomy. This paper provides relevant ecological concepts that bolster interdisciplinary links and offers recommendations for their application.